Relationship between Personal Characteristics and the Academic Performance of High School Students - Mishkevich A.M. (Психолого-педагогические исследования, 2021)
The influence of personality traits on performance at school is regularly researched in various studies, including meta-analytical studies. As personality traits are quite stable, they scarcely can be changed. According to the five-factor theory, the influence of inborn traits on behaviour is mediated by acquired characteristic adaptations. Which means that it is easier to change characteristic adaptations in order to correct behaviour, rather than traits. The survey was conducted among 135 Russian adolescents, ages from 14 to 17 (M=15.19; SD=0,71). The traits of the Big Five and four variations of reflexive characteristic adaptations were measured. Performance was also counted – the average score in all subjects for each student in the past academic year. As a result, we have found correlations of conscientiousness and openness with performance. This research has shown that reflexive characteristic adaptations are a more trustworthy performance correlate than traits. We have discovered that meta-attitude toward conscientiousness contributes, in a unique way, to performance at school. This contribution depended on neither gender differences nor the differences in the conscientiousness trait itself. The study has also revealed that the correlations between performance and openness can mostly be explained by gender differences. Whereas meta-attitude toward openness makes a significant contribution to the variation of successes in studying regardless of the gender differences and the differences in the openness treat itself. Thus, the research has shown, that reflexive characteristic adaptations contributes, in a unique way, to the prediction of performance at school.